Activation of periodate driven by the synergistic interaction between inherent soil Fe and organic matter for adiazine degradation: Mechanisms, soil-type effects, and soil property changes - Yue Zhang; Caixia Yan; Yabing Chen; Yuyan Liu; Mingjun Ding; Peng Wang; Haofeng Liu; Minghua Nie (Journal of Hazardous Materials, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

In situ conversion of KNiF3 perovskite into a fluoride-rich ion/electron-conducting interphase for stable sodium metal anodes - Runzhi Xu; Yiqing Lu; Rui Ding; Yi Li; Weiming Li; Mingjun Xu; Tingyan Gu; Yuqi Liu; Chuyu Tan (Chemical Engineering Journal, 2026)

Integrating spatiotemporal similarity for robust gap-filling in continuous surface water mapping with uncertainty quantification - Zhen Xiao; Runkui Li; Xianfeng Song; Mingjun Ding; Shunlin Liang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Impacts of long-term fertilizer reduction and organic substitution on microbe-mediated multi-nutrient in agricultural ecosystems - Zhenling Li; Jiawei Ying; Xiaokang He; Yangyang Li; Guangchun Shan; Chenghong Feng; Mingjun Ding; Gaoxiang Huang; Jia Liu (Agriculture, Ecosystems & Environment, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Synergistic effect between biochar and nanoscale zero valent iron effectively mitigated nitrous oxide emissions from a flooded paddy soil - Mingjun Ding; Yu Zhou; Zhe Li; Jian Zhang (Journal of Environmental Chemical Engineering, 2026)

Identification and evaluation of odor emissions from a petrochemical production area in China - Yunxia Feng; Jinchan Peng; Yirong Guo; Qingrun Li; Anshan Xiao; Rui Dong; Dewu Ding; Mingjun Li (Atmospheric Pollution Research, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Nitrogen transformation and N2O production pathways under arsenic and cadmium stress in Chongming Island, China - Yinghui Jiang; Guoyu Yin; Minghua Nie; Caixia Yan; Mingjun Ding; Hua Zhang; Mei Lei; Yong Ge (Marine Pollution Bulletin, 2025)

Agricultural plastic films reshape soil microplastic distribution, nitrogen cycle and ecological risks in facility agriculture - Hao Wang; Gaoxiang Huang; Xiaokang He; Guangchun Shan; Zhenling Li; Mingjun Ding; Chenghong Feng; Caixia Yan (Journal of Hazardous Materials, 2025)

Soil type-mediated root and leaf architectural modifications outweigh cadmium bioavailability in governing cadmium accumulation in rice - Gaoxiang HUANG; Jinbao ZHANG; Changfeng DING; Zhongyang XIONG; Jia LIU; Jingru HE; Haoyuan LÜ; Mingjun DING; Peng WANG; Yinghui JIANG; Lijun ZHOU; Zhenling LI (Pedosphere, 2025)

Cross-altitude distribution patterns of bacterial communities in Chinese rivers: evidence from meta-analysis - Ru Liu; Peng Wang; Qinwei Chen; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang (Environmental Research, 2025)

Rhizosphere microbiota modulate cadmium mobility dynamics and phytotoxicity in rice under differential Cd stress - Linxiu Cheng; Zhenling Li; Lijun Zhou; Jie Xie; Qiangqiang Zhou; Mingjun Ding; Peng Wang; Hua Zhang; Minghua Nie; Gaoxiang Huang (Plant and Soil, 2025)

Soil phosphorus availability regulates ecosystem carbon dynamics during the growing season of a typical temperate grassland in inner Mongolia, China - Jiayu Shi; Jirui Gong; Mingjun Ding; Siqi Zhang; Weiyuan Zhang; Xuede Dong (Journal of Arid Environments, 2025)

Thresholds for the relationships between soil trace elements and ecosystem multifunctionality in degraded alpine meadows - Yuping Wu; Mingjun Ding; Hua Zhang; Tiane Zou; Peng Huang; Huan Xu; Yueju Zhang; Huan Zeng; Jiaxin Xiong; Liyao Cheng; Linshan Liu; Yili Zhang (Agriculture, Ecosystems & Environment, 2025)

Mn-rich seedlings coupled with slow-release soil immobilization material effectively reduced cadmium accumulation in rice grain - Jinbao ZHANG; Zhongyang XIONG; Yurong WANG; Mingyue WU; Mingjun DING; Peng WANG; Zhenling LI; Gaoxiang HUANG (Pedosphere, 2025)

Selective enrichment of potential pathogens and antibiotic resistance genes derived from farmland residual microplastic films - Gaoxiang Huang; Hao Wang; Zhenling Li; Xiaokang He; Guangchun Shan; Peng Wang; Mingjun Ding; Chenghong Feng (Applied Soil Ecology, 2025)

Influence of the source and molecular weights on sulfathiazole/sulfadiazine binding in sedimentary dissolved organic matter - Caixia Yan; Fei Zhang; Minghua Nie; Yanqing Luo; Mingjun Ding; Shuhua Nie; John L. Zhou (Journal of Environmental Management, 2025)

Characterization and functional analysis of small heat shock protein gene HSP20.1 in Bombyx mandarina - Hui An; Jiaqi Ding; Enxi Chen; Ruonan Li; Mingjun Lin; Heying Qian; Guodong Zhao (International Journal of Tropical Insect Science, 2024)

Increasing human activity shifts the key spatial scale of landscape patterns on water quality from sub-basins to riparian zones - Jiawei Wen; Peng Wang; Yuanyang She; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Minghua Nie (Science of The Total Environment, 2024)

Differential response of heavy metal accumulation in freshwater aquatic organisms to organic matter pathway (δ13C) and trophic level (δ15N) - Huan Zeng; Xiang Xu; Mingjun Ding; Hua Zhang; Yinghui Jiang; Peng Wang; Gaoxiang Huang (Environmental Pollution, 2024)

Meadow degradation reduces microbial β diversity and network complexity while enhancing network stability - Yuping Wu; Ansheng Liang; Mingjun Ding; Hua Zhang; Huan Xu; Yueju Zhang (Applied Soil Ecology, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Spatial heterogeneity of soil moisture caused by drainage and its effects on cadmium variation in rice grain within individual fields - Gaoxiang Huang; Yu Wu; Linxiu Cheng; Dongmei Zhou; Xingxiang Wang; Mingjun Ding; Peng Wang; Yurong Wang (Science of The Total Environment, 2024)

Sediment nitrate dissimilatory reduction processes in the river-lake ecotone of Poyang Lake, China: Mechanisms and environmental implications - Yinghui Jiang; Zhenglei Xie; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Yun Cao; Guoyu Yin (Journal of Soils and Sediments, 2024)

Unveiling the hidden dynamics of intermittent surface water: A remote sensing framework - Zhen Xiao; Runkui Li; Mingjun Ding; Panli Cai; Jingxian Guo; Haiyu Fu; Xiaoping Zhang; Xianfeng Song (Remote Sensing of Environment, 2024)

Effect of pyrolysis temperature and molecular weight on characterization of biochar derived dissolved organic matter from invasive plant and binding behavior with the selected pharmaceuticals - Wangyu Wang; Minghua Nie; Caixia Yan; Yulong Yuan; Aoxue Xu; Mingjun Ding; Peng Wang; Min Ju (Environmental Pollution, 2024)

Spatio-temporal characteristics of farmland occupation of construction land expansion and its spatial relationship with grain yield in China for 2000–2020 - Zihua Li; Mingjun Ding; Kun Xie; Jingru Li; Liwen Chen (Journal of Geographical Sciences, 2024)

Characteristics of microplastic-derived dissolved organic matter and its binding with pharmaceuticals unveiled by fluorescence spectroscopy and two-dimensional correlation spectroscopy - Caixia Yan; Xiao Wang; Minghua Nie; Xiting Mo; Mingjun Ding; Jie Chen; Yi Yang (Science of The Total Environment, 2024)

Effects of dominant plant species change on soil multifunctionality in alpine meadows of the three-river source region - Liwen Chen; Mingjun Ding; Hua Zhang; Nengyu Wang; Yueju Zhang; Jiayi Wan; Kun Xie (Journal of Cleaner Production, 2024)

Visible light-mediated activation of periodate for bisphenol A degradation in the presence of Fe3+ and gallic acid at neutral pH - Yulong Yuan; Wangyu Wang; Minghua Nie; Caixia Yan; Peng Wang; Mingjun Ding (Chemical Engineering Journal, 2024)

Early–mid Holocene relative sea-level rise in the Yangtze River Delta, China - Yu Cheng; Shiyin Xu; Ding Luo; Bingfei Gao; Mingjun Zhu; Xinqing Zou (Marine Geology, 2023)

Reduced soil multifunctionality and microbial network complexity in degraded and revegetated alpine meadows - Bobo Wu; Mingjun Ding; Hua Zhang; Adam Thomas Devlin; Peng Wang; Lu Chen; Yueju Zhang; Yang Xia; Jiawei Wen; Linshan Liu; Yili Zhang; Minhuang Wang (Journal of Environmental Management, 2023)

Correction to: Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2023)

A meta-analysis reveals that geographical factors drive the bacterial community variation in Chinese lakes - Pengfei Gao; Peng Wang; Mingjun Ding; Hua Zhang; Gaoxiang Huang; Minghua Nie; Guangwei Wang (Environmental Research, 2023)

Degradation-driven bacterial homogenization closely associated with the loss of soil multifunctionality in alpine meadows - Yueju Zhang; Mingjun Ding; Hua Zhang; Nengyu Wang; Ziping Yu; Huan Xu; Peng Huang (Agriculture, Ecosystems & Environment, 2023)

Characterization of copper binding to biochar-derived dissolved organic matter: Effects of pyrolysis temperature and natural wetland plants - Caixia Yan; Wangyu Wang; Minghua Nie; Mingjun Ding; Peng Wang; Hua Zhang; Gaoxiang Huang (Journal of Hazardous Materials, 2023)

Potential of granular complexes of lime and montmorillonite for stabilizing soil cadmium and the underlying mechanisms - Gaoxiang Huang; Keyi Huang; Xingxiang Wang; Wuxing Shu; Wenjing Ren; Peng Wang; Hua Zhang; Minghua Nie; Mingjun Ding (Environmental Pollution, 2023)

Solar light promoted degradation of bisphenol s in carbonate/peroxymonosulfate system through accelerating singlet oxygen generation - Yulong Yuan; Minghua Nie; Caixia Yan; Leliang Wu; Wenbo Dong; Mingjun Ding; Peng Wang (Chemical Engineering Journal, 2023)

Hydrogen sulfite promoted the activation of persulfate by μM Fe2+ for bisphenol A degradation - Shiyao Chen; Caixia Yan; Minghua Nie; Leliang Wu; Mingjun Ding; Peng Wang (Environmental Science and Pollution Research, 2022)

Spectral characteristic of the waters with different sizes of particles: impact of water quality and land-use type - Zelan Lv; Peng Wang; Caixia Yan; Minghua Nie; Xiaoying Xiong; Mingjun Ding (Environmental Science and Pollution Research, 2022)

Bisphenol A adsorption behavior on soil and biochar: impact of dissolved organic matter - Yawen Deng; Caixia Yan; Minghua Nie; Mingjun Ding (Environmental Science and Pollution Research, 2021)

Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2020)

Regional differences in shifts of temperature trends across China between 1980 and 2017 - Lanhui Li; Yili Zhang; Qionghuan Liu; Mingjun Ding; Partho Protim Mondal (International Journal of Climatology, 2019)
As the climate system is known to be warming unevenly, the open question of whether there has been a significant warming “hiatus” at global or regional scales has attracted worldwide attention. With annual mean air temperature ( T mean ) setting new records subsequent to 2012, it is reasonable to reanalyse the presence of an apparent decelerated warming trend in China. We therefore examined the shifts of temperature trends in China between 1980 and 2017 using homogenized records from 798 meteorological stations via the Breaks For Additive Season and Trend (BFAST) method and Mann–Kendall and Sen's slope estimator statistical tests. The results show that T mean at the country level exhibited monotonic increase with a positive break occurring around 1997, and the warming rate during 1980–2017 (0.36 °C/decade) was slightly higher than that during 1980–1997, which suggests that this positive break did not overwhelm the overall continuous warming trend. Spatial records show that most areas west of 108°E or south of 30°N within the country experienced a continual warming trend over the study period and that negative break that occurred around 2010 was major contributor to temporary decelerated warming trend detected in other areas, especially in Northeast China. Hence, this study highlights annual air temperature has continued to rise overall in China since 1980, while considerable regional differences have been detected within the shifts of temperature trends.

Level, source identification, and risk analysis of heavy metal in surface sediments from river-lake ecosystems in the Poyang Lake, China - Hua Zhang; Yinghui Jiang; Mingjun Ding; Zhenglei Xie (Environmental Science and Pollution Research, 2017)

Spatial characterization, risk assessment, and statistical source identification of the dissolved trace elements in the Ganjiang River—feeding tributary of the Poyang Lake, China - Hua Zhang; Yinghui Jiang; Min Wang; Peng Wang; Guangxun Shi; Mingjun Ding (Environmental Science and Pollution Research, 2017)

Assessment of effectiveness of nature reserves on the Tibetan Plateau based on net primary production and the large sample comparison method - Yili Zhang; Zhongjun Hu; Wei Qi; Xue Wu; Wanqi Bai; Lanhui Li; Mingjun Ding; Linshan Liu; Zhaofeng Wang; Du Zheng (Journal of Geographical Sciences, 2016)

Start of vegetation growing season on the Tibetan Plateau inferred from multiple methods based on GIMMS and SPOT NDVI data - Mingjun Ding; Lanhui Li; Yili Zhang; Xiaomin Sun; Linshan Liu; Jungang Gao; Zhaofeng Wang; Yingnian Li (Journal of Geographical Sciences, 2015)

Spatial and temporal variability in the net primary production of alpine grassland on the Tibetan Plateau since 1982 - Yili Zhang; Wei Qi; Caiping Zhou; Mingjun Ding; Linshan Liu; Jungang Gao; Wanqi Bai; Zhaofeng Wang; Du Zheng (Journal of Geographical Sciences, 2014)

Heavy metal enrichment in the soil along the Delhi–Ulan section of the Qinghai–Tibet railway in China - Hua Zhang; Yili Zhang; Zhaofeng Wang; Mingjun Ding (Environmental Monitoring and Assessment, 2013)

The relationship between NDVI and precipitation on the Tibetan Plateau - Mingjun Ding; Yili Zhang; Linshan Liu; Wei Zhang; Zhaofeng Wang; Wanqi Bai (Journal of Geographical Sciences, 2007)

Vegetation change in the Mt. Qomolangma Nature Reserve from 1981 to 2001 - Wei Zhang; Yili Zhang; Zhaofeng Wang; Mingjun Ding; Xuchao Yang; Xuedong Lin; Linshan Liu (Journal of Geographical Sciences, 2007)

Land cover change along the Qinghai-Tibet Highway and Railway from 1981 to 2001 - Mingjun Ding; Yili Zhang; Zhenxi Shen; Linshan Liu; Wei Zhang; Zhaofeng Wang; Wanqi Bai; Du Zheng (Journal of Geographical Sciences, 2006)

Climate change in Mt. Qomolangma region since 1971 - Xuchao Yang; Yili Zhang; Wei Zhang; Yuping Yan; Zhaofeng Wang; Mingjun Ding; Duo Chu (Journal of Geographical Sciences, 2006)

Characteristics of grassland degradation and driving forces in the source region of the Yellow River from 1985 to 2000 - Linshan Liu; Yili Zhang; Wanqi Bai; Jianzhong Yan; Mingjun Ding; Zhenxi Shen; Shuangcheng Li; Du Zheng (Journal of Geographical Sciences, 2006)